Mycopathological Studies on Vigna radiata (L.) Wilczek (Green gram) from Patur, Dist. Akola (MS), India. - Chavhan, S T; Darade, M S; Devarkar, V D (Plantae Scientia, 2018)
Study of fungi infection from infected green gram plant was carried out in present identify. Various fungal pathogens were identified from green gram plants with respect to different localities and varieties at field condition. Selected samples were collected from regions of studied area. Total ten and eleven fungi were identified from two variety of green gram AKM-9911 and AKM-9904 respectively. Green gram (Vigna radiata (L.) Wiczek.) is one of the most widely used pulse crop of India. It is widely cultivated in Maharashtra, Uttar Pradesh, Gujarat, Tamil Nadu, Andhra Pradesh and Bihar. It is cultivated in many tropical and subtropical regions of the world including India and was also cultivated in ancient Indian.